Enhancing Water Awareness of Preservice Elementary Teachers through Local Water Sustainability Projects - Puji Winarti; Sri Haryani; Sri Wardani; Langlang Handayani (Universitas Pendidikan Ganesha, 2025)
The global water crisis demands education that fosters early water awareness, particularly through the role of elementary school teachers. This study aimed to evaluate the effectiveness of a local water sustainability project in enhancing water awareness among prospective elementary school teachers. A quasi-experimental pretest–posttest design with a mixed-methods approach was employed. Forty-two students participated in a series of contextual projects integrating knowledge, attitudes, and behaviors related to local water issues. An open-ended questionnaire was used as the research instrument. Quantitative analysis using a paired-sample t-test revealed significant improvements in knowledge (ΔM = 8.05), attitude (ΔM = 8.26), and behavior (ΔM = 8.83), with p < 0.001. Qualitative findings supported these results, showing a shift from basic understanding to more comprehensive knowledge, from passive attitudes to active commitment, and from inaction to real involvement in water conservation. The study concludes that implementing a local water sustainability project effectively enhances water awareness among future elementary school teachers. Overall, this model fosters comprehensive water awareness and supports the implementation of sustainable education at the elementary level.